Merging graphic design and multimedia features in digital interactive eBook for tourism purposes - Lee, L.S.; Ng, G.W.; Ooi, J.Z.; Oon, Y.B. (IEEE, 2016)
Tourism is becoming increasingly popular in many parts of the world. However, a visitor in a foreign country may feel anxious if information is display in a foreign travel guidebook. A phenomenon where tourist may face arbitrarily representation of an object by viewing the pictures and description has led to this paper entitle merging graphics design and multimedia features in digital interactive eBook for tourism purposes. The advantages of interactive eBook offered by computational technologies should widely be implemented instead of just adhere to paper book metaphor. This study aims to develop an eBook supported with active and interactive contents for tourism purposes.